Expression of tomato prosystemin gene in Arabidopsis reveals systemic translocation of its mRNA and confers necrotrophic fungal resistance. Issue 2 (3rd November 2017) - Zhang, Haiyan; Yu, Pengli; Zhao, Jiuhai; Jiang, Hongling; Wang, Haiyang; Zhu, Yingfang; Botella, Miguel A.; Šamaj, Jozef; Li, Chuanyou; Lin, Jinxing
Summary: Systemin (SYS), an octadecapeptide hormone processed from a 200‐amino‐acid precursor (prosystemin, PS), plays a central role in the systemic activation of defense genes in tomato in response to herbivore and pathogen attacks. However, whether PS mRNA is transferable and its role in systemic defense responses remain unknown. We created the transgenic tomato PS gene tagged with the green fluorescent protein ( PS‐GFP ) using a shoot‐ or root‐specific promoter, and the constitutive 35S promoter in Arabidopsis . Subcellular localization of PS‐/SYS‐GFP was observed using confocal laser scanning microscopy and gene transcripts were determined using quantitative real‐time PCR. In Arabidopsis, PS protein can be processed and SYS is secreted. Shoot‐/root‐specific expression of PS‐GFP in Arabidopsis, and grafting experiments, revealed that the PS mRNA moves in a bi‐directional manner. We also found that ectopic expression of PS improves Arabidopsis resistance to the necrotrophic fungus Botrytis cinerea, consistent with substantial upregulation of the transcript levels of specific pathogen‐responsive genes. Our results provide novel insights into the multifaceted mechanism of SYS signaling transport and its potential application in genetic engineering for increasing pathogen resistance across diverse plant families.